A robust single input adaptive sliding mode fuzzy logic controller for automotive active suspension system - Kucukdemiral, IB; Engin, SN; Omurlu, VE; Cansever, G (SPRINGER-VERLAG BERLIN, 2005)
The proposed controller in this paper, which combines the capability of fuzzy logic with the robustness of sliding mode controller, presents prevailing results with its adaptive architecture and proves to overcome the global stability problem of the control of nonlinear systems. Effectiveness of the controller and the performance comparison are demonstrated with chosen control techniques including PID and PD type self-tuning fuzzy controller on a quarter car model which consists of component-wise nonlinearities.
Keywords: SCHEME; Computer Science